Vinhos de mesa varietais de uvas americanas: análises químicas e energética - Uliana, Maíra Rodrigues [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP]; Oliveira, José Maria; Teixeira, José Antonio (EIA Energy in Agriculture, 2015)
The Brazilian wine industry has a remarkable characteristic that distinguishes from other markets, while the foreign market only accepts products originating from European varieties (Vitis vinifera), in Brazil, products originating from American varieties (Vitis labrusca and Vitis bourquina) and hybrids are also accepted. Dry and sweet varietal wines from varieties Bordô (dry and sweet), Isabel (sweet) e Máximo (dry) were analyzed, by the following chemical standard analyses: alcohol content; density; total and reduced dry matter; alcohol/reduced dry extract ratio; reducing sugars; total, volatile and fixed acidity; pH; total and free sulfur dioxide; and energy value. All analyzed wines presented results within the parameters set forth by Brazilian law, a positive fact, once they are commercialized. The varietal wine Máximo presented a low content of total and free sulfur dioxide, which may cause future problems with its sanity.

A indústria brasileira de vinhos tem uma característica notável que a distingui dos outros mercados. Enquanto o mercado estrangeiro só aceita produtos originários das variedades europeias (V. vinifera), no Brasil, produtos originários das variedades americanas (V. labrusca e V. bourquina) e híbridos também são aceitos. Vinhos varietais secos e suaves das variedades Bordô (seco e suave), Isabel (suave) e Máximo (seco), foram avaliados pelas seguintes determinações químicas: teor alcoólico; densidade; extrato seco total e reduzido; relação álcool em massa/extrato seco reduzido, açúcares redutores; acidez total, volátil e fixa; pH; dióxido de enxofre total e livre; e valor energético. Todos os vinhos analisados apresentaram resultados dentro dos parâmetros estipulados pela legislação brasileira, fato positivo, uma vez que são comercializados. O vinho varietal Máximo apresentou um teor baixo de dióxido de enxofre livre e total, podendo acarretar problemas futuros com sua sanidade.
Varietal table wines from american grapes: chemical and energy analisys
Keywords: Alcoholic beverages; Bordô; Isabella; Máximo; Bebida alcoólica; Bordô; Isabel; Máximo